Development of Molecularly Imprinted Polymers for Detection of Malachite Green in Cultured Tilapia (Oreochromis Mossambicus) and Catfish (Clarias Batrachus) - Lok, Chui Mei (2009)
Malachite green (MG) is a synthetic dye used for dying leather, silk, cotton and paper. It has been used illegally to treat fungal infection on fish and it persists in fish tissue for relatively long time. Research indicates that MG is carcinogenic. Molecularly imprinted polymers (MIPs) offer an attractive alternative to the conventional detection methods, for example high performance liquid chromatography and liquid chromatography-ion trap mass spectrometry, which are time-consuming and tedious. Molecularly imprinting technology (MIT) is a technique where the polymers are synthesized in the presence of target molecule which acts as the template. The MIPs can specifically bind the target molecule in preference to other closely related molecules. Therefore, the aim of this study was to develop the MIPs targeting MG in order to detect its presence in seafood. A series of MIPs were prepared using MG as the template molecules by non-covalent bulk polymerization. MG, methacrylic acid, ethylene glycol dimethacrylate, azobisisobutyronitrile and acetonitrile were used as template, functional monomer,crosslinker, initiator and porogen respectively. Their physical properties have been characterized using scanning electron microscope. The rebinding capability and selectivity have been evaluated. In the rebinding analysis, the MG adsorption amount increased with the increasing of MG concentration, where the MIPs bound more MG comparing with the control non-imprinted polymers (NIPs). Scatchard plot’s analysis revealed that there was one class of binding sites populated in the imprinted polymers with maximum adsorption capacity of MG of 0.491-0.906 μmol/g and dissociation constants were estimated to be 9.091-20.000 μmol/L. The selectivity test showed that the MIPs could specifically bind the MG comparing with methyl violet,which is structurally similar to the MG. The imprinting factor was in the range of 1.59-1.88. The MIPs have showed ability to rebind MG in walking catfish (Clarias batrachus) and tilapia (Oreochromis mossambicus) for the real sample analysis. MIPs that were synthesized with the presence of MG showed desired results, where their rebinding ability and specificity were better compared with the control NIPs. The data and method will serve as crucial knowledge for the development of MIP biosensor for MG detection in the future study.